Establishment of neural stem cell culture from the central nervous system of the Iberian ribbed newt Pleurodeles waltl. (17th November 2022) - Seki‐Omura, Ryohei; Hayashi, Shinichi; Oe, Souichi; Koike, Taro; Nakano, Yousuke; Hirahara, Yukie; Tanaka, Susumu; Kitada, Masaaki
Abstract: Urodele amphibians have exceptional regeneration ability in various organs. Among these, the Iberian ribbed newt ( Pleurodeles waltl ) has emerged as a useful model organism for investigating the mechanisms underlying regeneration. Neural stem cells (NSCs) are an important source of regeneration in the central nervous system (CNS) and their culture method in vitro has been well established. NSCs form spherical cell aggregates called neurospheres and their formation has been demonstrated in various vertebrates, including some urodele species, but not in P. waltl . In this study, we reported neurosphere formation in brain‐ and spinal cord‐derived cells of post‐metamorphic P. waltl . These neurospheres showed proliferative activity and similar expression of marker proteins. However, the surface morphology was found to vary according to their origin, implying that the characteristics of the neurospheres generated from the brain and spinal cord could be similar but not identical. Subsequent in vitro differentiation analysis demonstrated that spinal cord‐derived neurospheres gave rise to neurons and glial cells. We also found that cells in neurospheres from P. waltl differentiated to oligodendrocytes, whereas those from axolotls were reported not to differentiate to this cell type under standard culture conditions. Based on our findings, implantation of genetically modified neurospheres together with associated technical advantages in P. waltl could reveal pivotal gene(s) and/or signaling pathway(s) essential for the complete spinal cord regeneration ability in the future. Abstract : We report the formation of spherical cell aggregates similar to neurospheres in vitro from the brain and spinal cord of post‐metamorphic Pleurodeles waltl . These aggregates expressed several marker proteins of neural stem cells, and cells in the aggregates could differentiate into neurons, astrocytes, and oligodendrocytes in vitro . Based on our findings, we conclude that the observed spherical cell aggregates could be regarded as neurospheres from the central nervous system of P. waltl .